2015
DOI: 10.1051/ocl/2015006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pedoclimatic and agricultural conditions on sunflower seeds characteristics in relation to the dehulling process

Abstract: -Dehulling sunflower seeds can increase meal protein content by up to 35-36%. However, high variability in seed quality constitutes an obstacle to optimizing the dehulling process. This study has sought to identify the parameters that influence the protein content of sunflower seeds and the ease with which they can be dehulled. Genetic, climatic and crop management effects were studied using seed samples taken from farmers' fields in south-west France. Soil and climatic effects were revealed to be important fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…This can be explained by the fact that breeding programmes have not searched for variability in protein content. No relationship has been observed between oil content and protein content as a percentage of DDM (Dauguet et al, 2015). So, the independence of these 2 features would suggest that there is considerable scope for improving the protein content of the defatted fraction without penalizing oil content.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…This can be explained by the fact that breeding programmes have not searched for variability in protein content. No relationship has been observed between oil content and protein content as a percentage of DDM (Dauguet et al, 2015). So, the independence of these 2 features would suggest that there is considerable scope for improving the protein content of the defatted fraction without penalizing oil content.…”
mentioning
confidence: 97%
“…These are the two criteria that are currently taken into account in the registration of new sunflower varieties; protein content is not a criterion in the registration of new sunflower varieties and nor is it measured in the official trials. Studies have shown that soil and climatic conditions exert a greater influence on protein content than genetics (Dauguet et al, 2015;Nel, 2001;Oraki et al, 2011). This can be explained by the fact that breeding programmes have not searched for variability in protein content.…”
mentioning
confidence: 99%
See 3 more Smart Citations